ELECTROCHEMICAL TECHNIQUES IN ENERGY STORAGE: ADVANCES IN SUPERCAPACITORS - Catherine Lie; Samantha Gonzales; Dina Ahmed (Yayasan Adra Karima Hubbi, 2025)
has driven significant advancements in electrochemical techniques, particularly in the development of supercapacitors. These devices offer rapid charge and discharge capabilities, making them suitable for various applications, including renewable energy systems and electric vehicles. This study aims to explore the recent advancements in supercapacitor technology through the application of novel electrochemical techniques. The focus is on improving energy density, power density, and cycle life to enhance the overall performance of supercapacitors. A comprehensive review of recent literature was conducted, highlighting innovative materials and techniques used in supercapacitor design. Experimental work involved synthesizing new electrode materials and characterizing their electrochemical performance using techniques such as cyclic voltammetry and electrochemical impedance spectroscopy. Findings indicate that the integration of advanced materials, such as graphene and metal-organic frameworks (MOFs), significantly enhances the electrochemical performance of supercapacitors. The study demonstrated improvements in energy density by up to 50% and power density by 30%, along with extended cycle life under various operational conditions.